Suboptimal Tongue Pressure Is Associated with Risk of Malnutrition in Community-Dwelling Older Individuals - Chang, Ke-Vin; Wu, Wei-Ting; Chen, Lan-Rong; Wang, Hsin-I; Wang, Tyng-Guey; Han, Der-Sheng (Nutrients, 2021)
The tongue plays an important role in swallowing, and its dysfunction theoretically leads to inadequate oral intake and subsequent malnutrition. This study aimed to explore how different levels of tongue pressure are related to malnutrition among community-dwelling older individuals. The target population was community-dwelling adults aged ≥ 65 years. Tongue pressure was measured using the Iowa Oral Performance Instrument, whereas the mini nutrition assessment (MNA) test was administered to determine the nutritional status. A full MNA score of less than 24 points was defined as risk of malnutrition. Multivariate logistic regression analyses were conducted to calculate the odds ratio (OR) of risk of malnutrition among different quartiles of tongue pressure. Among the 362 participants, 26 (7.1%) were classified as having risk of malnutrition. Body weight, body mass index, handgrip strength, skeletal muscle mass index, sum MNA score, and serum levels of albumin were lower in the malnutrition risk groups than in the normal nutrition status group. A positive correlation was identified between tongue pressure and the MNA score (r = 0.143, p < 0.01). Treating the subgroup of the highest quartile of tongue pressure as the reference, the crude odds ratio (OR) of having risk of malnutrition was 5.37 (95% CI, 1.14–25.28) in the subgroup at the third quartile, 3.10 (95% CI, 0.60–15.84) in the subgroup at the second quartile, and 3.95 (95% CI, 0.81–19.15) in the subgroup at the lowest quartile. After adjustment for age and sex, the subgroup in the third quartile still presented with a significantly higher risk (OR, 4.85; 95% CI, 1.02–22.99) of risk of malnutrition. Compared with the subgroup at the highest quartile of tongue pressure, the crude OR for all the subgroups in the lower three quartiles was 4.17 (95% CI, 0.96–18.04), showing borderline significance (p = 0.05). In conclusion, we found hints for an association between decreased tongue pressure and an increased risk of malnutrition in community-dwelling older individuals. Older people with suboptimal tongue pressure should undergo a thorough assessment of their nutritional status and swallowing function for the early identification of subclinical malnutrition and dysphagia.